Reactions of azoalkenes derived from hydrazones of ethyl bromopyruvate with electron rich alkenes and heterocycles - Clarke, S (1991)
Three hydrazones of ethyl bromopyruvate, the dinitrophenylhydrazone 2a, the toluene-4-sulphonylhydrazone 2b and the t-butoxycarbonylhydrazone 2c, have been reacted with a series of nucleophilic alkenes and heterocycles in the presence of sodium carbonate. Azoalkenes 3 are presumed as intermediates and adducts have been isolated. The azoalkenes derived from hydrazones 2a and 2c are found to be useful electrophiles and electrophilic dienes.